Chronic low-frequency rTMS of primary motor cortex diminishes exercise training-induced gains in maximal voluntary force in humans - Hortobágyi, Tibor; Richardson, Sarah Pirio; Lomarev, Mikhael; Shamim, Ejaz; Meunier, Sabine; Russman, Heike; Dang, Nguyet; Hallett, Mark (East Carolina University, 2009)
Although there is consensus that the central nervous system mediates the increases in maximal voluntary force (maximal voluntary contraction, MVC) produced by resistance exercise, the involvement of the primary motor cortex (M1) in these processes remains controversial. We hypothesized that 1-Hz repetitive transcranial magnetic stimulation (rTMS) of M1 during resistance training would diminish strength gains. Forty subjects were divided equally into five groups. Subjects voluntarily (Vol) abducted the first dorsal interosseus (FDI) (5 bouts 10 repetitions, 10 sessions, 4 wk) at 70–80% MVC. Another group also exercised but in the 1-min-long interbout rest intervals they received rTMS [Vol rTMS, 1 Hz, FDI motor area, 300 pulses/ session, 120% of the resting motor threshold (rMT)]. The third group also exercised and received sham rTMS (Vol Sham). The fourth group received only rTMS (rTMS_only). The 37.5% and 33.3% gains in MVC in Vol and Vol Sham groups, respectively, were greater (P 0.001) than the 18.9% gain in Vol rTMS, 1.9% in rTMS_only, and 2.6% in unexercised control subjects who received no stimulation. Acutely, within sessions 5 and 10, single-pulse TMS revealed that motor-evoked potential size and recruitment curve slopes were reduced in Vol rTMS and rTMS_only groups and accumulated to chronic reductions by session 10. There were no changes in rMT, maximum compound action potential amplitude (Mmax), and peripherally evoked twitch forces in the trained FDI and the untrained abductor digiti minimi. Although contributions from spinal sources cannot be excluded, the data suggest that M1 may play a role in mediating neural adaptations to strength training. Originally published in Journal of Applied Physiology Vol. 106, 2009.
Keywords: Muscles; Transcranial magnetic stimulation; Cortical excitability